The Impact of Social Media on the Reduction of Corporate Irresponsibility (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This research paper explores the influence of social media platforms on corporate behavior and accountability. It investigates how social media has empowered consumers, activists, and journalists to expose and challenge corporate misconduct, leading to increased transparency, pressure for ethical practices, and ultimately, a reduction in corporate irresponsibility. By analyzing case studies of high-profile corporate scandals and examining the role of social media in these events, the paper aims to shed light on the potential of social media as a tool for promoting corporate responsibility and accountability. This work provides a comprehensive analysis of the subject matter by identifying and assessing prior research, summarizing the findings of those studies, and highlighting knowledge gaps. Moreover, it offers recommendations regarding the manner in which the situation should progress. The current web and social media enable an ideology that extols capitalism while failing to recognize the predominant influence of capitalist interests on the Internet. These platforms encourage participation, incite revolutions, support democracy, and expand the public sphere, all while facilitating an ideology that is pro-capitalism.